Doses to organs at risk calculated using plato and oncentra softwares in intracavitary brachytherapy - Nor Hafizah Abdullah; Mazurawati Mohamad; Reduan Abdullah; Ahmad Zakaria; Chen, Suk Chiang (Penerbit Universiti Kebangsaan Malaysia, 2021)
This is a retrospective study, the organ doses of the bladder and the rectum were compared between routine PLATO V14.2.3 (Nucletron B.V., Veenendaal, The Netherlands) and newer version software Oncentra MasterPlan (OMP) V4.3 (Nucletron B.V., Veenendaal, The Netherlands) treatment planning systems (TPS). The treatment data of 32 intracavitary brachytherapy patients at Hospital Universiti Sains Malaysia from January 2010 to June 2015 were used. These data sets were used for catheter reconstruction for both PLATO and OMP TPS followed by independent verification using Excel. There was no significant difference in mean doses to organs at risk (OARs) that calculated by both TPS (p>0.05). The mean percentage of doses calculated by PLATO TPS for bladder and rectum were 66.58 ± 27.42% and 46.27 ± 14.47%, respectively. While, the mean percentage of doses for bladder and rectum calculated by OMP TPS were 65.68 ± 24.24% and 46.46 ± 16.66%, respectively. The mean percentage difference in doses comparison between independent verification calculation and PLATO TPS was 1.96 ± 6.00% and then became 6.37 ± 5.17% when it was compared with OMP TPS. Overall, the dose calculation differences for both versions of TPS were within the range recommended by Nuclear Regulatory Commission (NRC). The dose calculations of the two treatment planning systems showed good agreement and both could be used in planning intracavitary brachytherapy for cervical cancer. Whereas, Excel based independent verification is suitable to be implemented as routine dose verification programme prior to treatment delivery.